Mitral Regurgitation and Body Mass Index Increase the Predictability of Perioperative Bleeding in Anticoagulated Patients With Nonvalvular Atrial Fibrillation - Huang, Hao; Cai, Chi; Hua, Wei; Zhang, Nixiao; Niu, Hongxia; Chen, Xuhua; Wang, Jing; Jia, Yuhe; Chu, Jianmin; Tang, Min; Zhang, Shu (Frontiers in Cardiovascular Medicine, 2022)
Background Catheter ablation (CA) effectively restores sinus rhythm in atrial fibrillation (AF) but causes a short-term fluctuation in the coagulation state. Potential risk factors and better management during this perioperative period remain understudied. Methods We consecutively included 940 patients with nonvalvular AF who received CA at Fuwai Hospital, Beijing, China. Patients were divided into two groups according to their bleeding status during 3 months' anticoagulation. Any adverse events related to bleeding in the 3 months were evaluated. The HAS-BLED score and ABC-bleeding score, as well as other potential factors, were explored to predict bleeding risk. Results In this observational study, 8.0% and 0.9% of the whole population suffered from bleeding and thromboembolic events, respectively. After adjusting for known factors related to bleeding, mitral regurgitation (MR, p for trend <0.001) and body mass index (BMI, odds ratio (OR) = 0.920, 95% CI 0.852–0.993, p = 0.033) were the most significant ones. C-indexes of the HAS-BLED score and ABC-bleeding score for bleeding were 0.558 (0.492–0.624) and 0.585 (0.515–0.655), respectively. The incorporation of MR and BMI significantly improved the predictive value based on HAS-BLED score (C-index = 0.650, 95% CI 0.585–0.715, p = 0.004) and ABC-bleeding score (C-index = 0.671, 95% CI 0.611–0.731, p < 0.001). The relative risk of mild-moderate MR was 4.500 (95% CI 1.625–12.460) in patients with AF having HAS-BLED = 1 and 4.654 (95% CI 1.496–14.475) in HAS-BLED ≥ 2, while it was not observed in patients with HAS-BLED = 0 (p = 0.722). Conclusion More severe MR and lower BMI are associated with a higher incidence of perioperative bleeding, which helps improve the predictability of increased individual bleeding risk of a patient with nonvalvular AF who has received CA therapy and oral anticoagulants.